2013
DOI: 10.2220/biomedres.34.23
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of freshly isolated adipose tissue-derived regenerative cells enhances angiogenesis in a murine model of hind limb ischemia

Abstract: Therapeutic angiogenesis has emerged as one of the most promising therapies for severe ischemic cardiovascular diseases with no optional therapy. Several investigators have reported that transplantation of cultured adipose-derived regenerative cells (cADRCs) to ischemic tissues promotes neovascularization and blood perfusion recovery; however, cell therapy using cultured cells has several restrictions. To resolve this problem, the angiogenic capacity of freshly isolated ADRCs (fADRCs) obtained from Lewis rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 25 publications
2
29
0
Order By: Relevance
“…ADRCs expressing GLUT1, 3 and 4 uptake excess markers such as CD13, CD49, CD44, CD90, and CD105 (18). We previously found that although freshly isolated ADRCs included CD31, CD34, and CD45 positive cells, CD90 positive cells became predominant during culture, which indicated proliferation of only mesenchymal cells during culture (5). Under hyperglycemic conditions the predominance of CD90 positive cells was not affected, indicating that hyperglycemia does not influence the subpopulation of ADRCs.…”
Section: Discussionmentioning
confidence: 89%
“…ADRCs expressing GLUT1, 3 and 4 uptake excess markers such as CD13, CD49, CD44, CD90, and CD105 (18). We previously found that although freshly isolated ADRCs included CD31, CD34, and CD45 positive cells, CD90 positive cells became predominant during culture, which indicated proliferation of only mesenchymal cells during culture (5). Under hyperglycemic conditions the predominance of CD90 positive cells was not affected, indicating that hyperglycemia does not influence the subpopulation of ADRCs.…”
Section: Discussionmentioning
confidence: 89%
“…ASCs were enzymatically isolated from the inguinal subcutaneous fat tissue of rats and cultured as previously described (3). Skeletal myoblasts were isolated from the skeletal muscle of the thigh as described previously (17).…”
Section: In Vitro Studymentioning
confidence: 99%
“…Interestingly, ASC sheets expressed significantly higher mRNA and protein levels of HGF, VEGF, and bFGF than myoblast cell sheets under hypoxic condition, associated with the less prevalence of cell apoptosis in ASC sheets than myoblast cell sheets. bFGF also augments neovascularization and inhibits cellular apoptosis (3,21). Since preventing apoptosis of transplanted cells leads to improvement of Fig.…”
Section: Measurement Of Cardiac Function In Isolated Perfused Heartsmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantage of ASCs includes their relative abundance, rapid expansion, multipotency and low immunogenicity as compared with other mesenchymal stromal cells [Gimble, 2003;Huang et al, 2004]. Transplanting ASCs induces neovascularization and improves blood flow to ischemic tissue in animal models [Sumi et al, 2007;Harada et al, 2013]. However, less research has been conducted on transplanted xenogeneic ASCs to determine whether endothelial differentiation is evident [Gong et al, 2014].…”
Section: Introductionmentioning
confidence: 99%